Managing your working capital - Ibitoye, S. O. (Ibadan : University Press Limited, 1993)
This book derives its title from the article is intended primarily for the practicing manager, director or any other person who has responsibility for the management of business resources.
Includes index
hza 04/10/2018
Loans
Keywords: Management accounting